2004
DOI: 10.1111/j.1600-079x.2004.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the antioxidative effects of melatonin at the mitochondrial level during oxidative stress‐induced apoptosis of rat brain astrocytes

Abstract: Oxidative stress-induced mitochondrial dysfunction has been shown to play a crucial role in the pathogenesis of a wide range of diseases. Protecting mitochondrial function, therefore, is vital for cells to survive during these disease processes. In this study, we demonstrate that melatonin, a chief secretory product of the pineal gland, readily rescued mitochondria from oxidative stress-induced dysfunction and effectively prevented subsequent apoptotic events and death in rat brain astrocytes (RBA-1). The earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
207
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(226 citation statements)
references
References 61 publications
17
207
1
1
Order By: Relevance
“…Cellular dysfunction via this mechanism is likely to reflect in decreased respiratory function and the accumulation of mtDNA defects. By contrast, more severe ROS damage to mitochondria elicits the apoptosis pathway (41)(42)(43)(44). Generation of ROS by photo-irradiation can lead to mitochondrial swelling (45), increased mitochondrial calcium levels (43), and Bcl-2 inhibition and mitochondrial matrix caspase-2 and -9 activation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular dysfunction via this mechanism is likely to reflect in decreased respiratory function and the accumulation of mtDNA defects. By contrast, more severe ROS damage to mitochondria elicits the apoptosis pathway (41)(42)(43)(44). Generation of ROS by photo-irradiation can lead to mitochondrial swelling (45), increased mitochondrial calcium levels (43), and Bcl-2 inhibition and mitochondrial matrix caspase-2 and -9 activation (44).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, more severe ROS damage to mitochondria elicits the apoptosis pathway (41)(42)(43)(44). Generation of ROS by photo-irradiation can lead to mitochondrial swelling (45), increased mitochondrial calcium levels (43), and Bcl-2 inhibition and mitochondrial matrix caspase-2 and -9 activation (44). To complicate matters further, there is some evidence that the ROS-mtDNA damage axis can be regulated via growth factors and altered transcription factor activities (12,46).…”
Section: Discussionmentioning
confidence: 99%
“…First, it increases the activities of mitochondrial respiratory complexes I and IV in a time dependent manner [57]. This effect of melatonin, namely the improvement of electron transport capacity in mitochondria, is remarkable as these effects are observed in senescence-accelerated mice [58]. In addition to this, other processes perturbing the mitochondrial membrane potential such as calcium overload are also antagonized by melatonin.…”
Section: Molecular Mechanisms Of Melatonin's Antiamyloid Actionsmentioning
confidence: 98%
“…The different regulatory mechanisms of apoptosis and their modification by treatment with melatonin were tested in different cells after irradiation. It is found that the mitochondrial pathway was strongly influenced by melatonin by reducing mitochondrial ROS generation and calcium release as well as inhibiting the opening of the MPTP as shown in rat brain astrocytes (Jou et al 2004), mouse striatal neurons (Andrabi et al 2004) and rat cerebellar granule neurons (Han et al 2006). Moreover, the prevented decreases in the mitochondrial membrane potential resulted from irradiation suggests that melatonin, due to its physiochmeical characters crosses the bloodbrain barrier and biological membranes to easily reach mitochondria, stabilizes oxidative stress-mediated dysfunction and integrity of mitochondria by preserving its membrane potential and increasing the efficiency of mitochondrial electron transfer chain and ATP synthesis (Acuna-Castroviejo et al 2001).…”
Section: Melatonin Modulates Apoptosis In Radiotherapy and Space Radimentioning
confidence: 99%